Cote d'Ivoire : 2011 Article IV Consultation and Requests for a Three-Year Arrangement Under the Extended Credit Facility and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries: Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report, 2011)
This 2011 Article IV Consultation reviews Cote d'Ivoire's economic condition. Cote d'Ivoire is emerging from a decade-long sociopolitical crisis that has held back its economic growth. In 2009, Cote d'Ivoire adopted an economic and financial program supported by a three-year Extended Credit Facility (ECF) arrangement with the aim of ensuring a stable macroeconomic framework, promoting sustained growth, and reducing poverty. Executive Directors have commended Cote d'Ivoire's rapid progress in reviving the economy. Directors have also welcomed the authorities' good performance under the economic recovery program, especially the prudent budgetary stance.